Variability and trends of Arctic water vapour from passive microwave satellites Special role of Polar lows and Atmospheric rivers - Radovan, Ana (2021)
Water in the vapour phase is the most important component of the hydrological cycle. It is formed by processes of evaporation and sublimation during which a lot of energy as latent heat is absorbed from the atmosphere. Through atmospheric large and small scale circulation, this energy is transported and released elsewhere through the process of condensation. Water vapour is the most important greenhouse gas (GHG) due to its abundance and its effectiveness in absorbing longwave radiation. In the light of global climate change, it is of great importance to identify trends of water vapour amounts in the atmosphere and its variability. Climate change in terms of the near-surface temperature is most pronounced in the Arctic, known as Arctic Amplification. Since most of the Arctic are either open ocean or sea-ice covered surfaces, only sparse ground-based observations, mostly confined to land areas are available. Therefore, one must resort to usage of the satellite based observations which offer a great advantage by their large spatial coverage. For water vapour assessment, passive microwave satellites are well suited due to their ability to sense water vapour under clear and cloudy sky conditions independent of sun light. A number of products of integrated water vapour (IWV) from various satellites are available. However, these are often inconsistent and prone to have biases due to various assumptions and uncertainties of a priori data included in the retrieval algorithms. According to the Clausius-Clapeyron relation, water vapour is constrained by the saturation vapour pressure which is constrained only by the temperature. Therefore, this thesis investigates the hypothesis that brightness temperatures (Tbs) from spaceborne passive microwave instruments can be used as a proxy for water vapour trends. To test this hypothesis, satellites based Tbs are compared to synthetic Tbs derived from the Arctic System Reanalysis (ASR). To enable the comparison, the ASR has been evaluated in Tb space by employing the Passive and ...